2016
DOI: 10.3390/ijms17101757
|View full text |Cite
|
Sign up to set email alerts
|

Differential Amino Acid, Carbohydrate and Lipid Metabolism Perpetuations Involved in a Subtype of Rheumatoid Arthritis with Chinese Medicine Cold Pattern

Abstract: Pattern classification is a key approach in Traditional Chinese Medicine (TCM), and it is used to classify the patients for intervention selection accordingly. TCM cold and heat patterns, two main patterns of rheumatoid arthritis (RA) had been explored with systems biology approaches. Different regulations of apoptosis were found to be involved in cold and heat classification in our previous works. For this study, the metabolic profiling of plasma was explored in RA patients with typical TCM cold or heat patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Taurine and hypoxanthine are related to oxidative damage and are the direct scavenger of reactive oxygen radicals. It has been reported that the level of reactive oxygen species in plasma was significantly increased in RA patients (Madsen et al, 2011 ; Guo et al, 2016 ). Hence, the increased levels of taurine and hypoxanthine might be the defense mechanism against oxidative damage.…”
Section: Discussionmentioning
confidence: 98%
“…Taurine and hypoxanthine are related to oxidative damage and are the direct scavenger of reactive oxygen radicals. It has been reported that the level of reactive oxygen species in plasma was significantly increased in RA patients (Madsen et al, 2011 ; Guo et al, 2016 ). Hence, the increased levels of taurine and hypoxanthine might be the defense mechanism against oxidative damage.…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggested that none of the treatments truly cures RA, as the underlying pathology of the RA was not fully reversed. Several other reports also demonstrated metabolic alterations in RA patients [8][9][10][11][12] (Table 1). These data suggested that metabolic changes are closely associated with inflammation in RA patients and may represent a potential target for disease monitoring and personalized medication for RA.…”
Section: Metabolomics In Rheumatoid Arthritismentioning
confidence: 63%
“…Carnitine and acylcarnitine supplementation may be benecial for cold RA patients, but less for hot RA patients. 22 The differences in the biological backgrounds (genes, proteins, and metabolites) of patients with RA cold and hot symptoms have been reported in the study system, 23,24 and these results broaden the prospect of personalized RA treatment.…”
Section: Ra Exposition Based On Tcm Theorymentioning
confidence: 90%